PENGEMBANGAN MODUL AJAR DIGITAL PEMBUATAN FILM PENDEK UNTUK PENGUATAN KARAKTER SISWA MATA PELAJARAN INFORMATIKA KELAS XI SMA KRISTEN CITRA BANGSA MANDIRI KUPANG - Ivander Christian Djami Ga; Maria M. B. Sogen; Diana Yanni Ariswati Fallo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Development of Digital Teaching Modules for Short Film Making to Strengthen the Character of Students in the Informatics Subject for Grade XI at Citra Bangsa Mandiri Christian High School in Kupang. Informatics Education Study Programme, Faculty of Teacher Training and Education, Citra Bangsa University, Kupang. Supervisors: Dr Maria M. B. Sogen, S.Kom., M.Pd, Diana Yanni Ariswati Fallo, S. Kom., M.T. This study aims to develop a digital teaching module on short film making, which not only improves students' understanding of the short film making process (pre-production to distribution) but also strengthens character values through a collaborative project-based approach. The method used was Research and Development (R&D) with the ADDIE model (Analyse, Design, Development, Implementation, Evaluation), conducted at Citra Bangsa Mandiri Christian High School in Kupang with a sample of 37 students from classes XI C and XI H (saturation sampling technique). Data collection techniques included tests (pre-test and post-test), questionnaires, interviews, observations, and documentation, analysed using descriptive statistics, N-Gain Score, and Likert scale. The results showed that the digital teaching module was effective, with an increase in the average pre-test score (58.95–63.89) to the post-test score (90.28–92.89), an N-Gain of 78.68% (high category), and expert validation (material: 86.67%; media: 88.33%; practitioners: 96.67%) 91% character building questionnaire and student response 79.95% (acceptable). This module has been proven to improve student understanding and character building through collaborative activities, in accordance with the Merdeka Curriculum. The conclusion of the study is that the digital teaching module for short film making is feasible and effective as an innovative learning medium to support character building in students in Informatics learning.